Neon's secret universe - Pounder, Sibeal (London ; Bloomsburry, 2022)
Unicorns are NOT horse creatures with horns. In fact, they are the most powerful magical beings on the planet and they look just like you and me. They live in a secret realm known as the Universe, and the horse with a horn thing was just something a unicorn called Greg made up to distract the humans - and it really worked! But a young human girl called Neon Gallup is about to find the last remaining Universe portal opener (an old, battered green lipstick) and step into a zany world where magic is made with goo and the possibilities are endless! Unfortunately, if there was one person you wouldn't want keeping the greatest magical secret of all time, it would be Neon Gallup ..